2018
DOI: 10.1002/joc.5539
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of measurement errors to reconcile precipitation distribution in the high‐altitude Indus basin

Abstract: Precipitation in the high-altitude Indus basin governs its renewable water resources affecting water, energy and food securities. However, reliable estimates of precipitation climatology and associated hydrological implications are seriously constrained by the quality of observed data. As such, quantitative and spatiotemporal distributions of precipitation estimated by previous studies in the study area are highly contrasting and uncertain. Generally, scarcity and biased distribution of observed data at the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 72 publications
(182 reference statements)
5
70
1
Order By: Relevance
“…Several climate studies of the Indus have focused on using lower-elevation precipitation gauges, which are then used to spatially interpolate basin-wide precipitation. Dahri et al (2016) and Dahri et al (2018) have assembled perhaps the largest collection of climatological measurements covering the AKAH region, mostly based on gauge measurements, as part of a study on the hydrometeorology of the Indus Basin. Using undercatch corrections based on wind, often from reanalysis, they increased precipitation estimates by 21 % on average throughout the Indus Basin (Dahri et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several climate studies of the Indus have focused on using lower-elevation precipitation gauges, which are then used to spatially interpolate basin-wide precipitation. Dahri et al (2016) and Dahri et al (2018) have assembled perhaps the largest collection of climatological measurements covering the AKAH region, mostly based on gauge measurements, as part of a study on the hydrometeorology of the Indus Basin. Using undercatch corrections based on wind, often from reanalysis, they increased precipitation estimates by 21 % on average throughout the Indus Basin (Dahri et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dahri et al (2016) and Dahri et al (2018) have assembled perhaps the largest collection of climatological measurements covering the AKAH region, mostly based on gauge measurements, as part of a study on the hydrometeorology of the Indus Basin. Using undercatch corrections based on wind, often from reanalysis, they increased precipitation estimates by 21 % on average throughout the Indus Basin (Dahri et al, 2018). For example, in the Gilgit sub-basin, they find an unadjusted precipitation estimate of 582 mm yr −1 , adjusted to 787 mm yr −1 , a 35 % increase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, a comprehensive evaluation of the basin-wide water cycle is needed. Studies that have addressed this issue have stressed the uncertainties inherent in the observed precipitation (Singh et al, 2011;Gardelle et al, 2012;Immerzeel et al, 2015;Wang et al, 2017;Dahri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beside the risk of corruption or missing values in the reporting process, it has been demonstrated that rain gauges can underestimate precipitation (Sevruk, 1984;Goodison et al, 1989). The main source of underestimation is the wind-driven under-catchment that can reach up to 50 % during snowfall (Goodison et al, 1989;Adam and Lettenmaier, 2003;Wolff et al, 2015;Dahri et al, 2018), but also includes the wetting of the instrument, evaporation before measuring, and splashing out (WMO, 2008). Dahri et al (2018) used the guidelines from the World Meteorological Organization (WMO) to re-evaluate the precipitation measured from hundreds of rain gauges in the upper Indus and found the underestimation to be between 1 % and 65 % for each station, and 21 % across the basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation